Acute and Long-Term Effects of Concurrent Resistance and Swimming Training on Swimming Performance - Gavriil Arsoniadis; Petros Botonis; Gregory C. Bogdanis; Gerasimos Terzis; Argyris Toubekis (MDPI AG, 2022)
Dry-land resistance exercise (RT) is routinely applied concurrent to swimming (SWIM) training sessions in a year-round training plan. To date, the impact of the acute effect of RT on SWIM or SWIM on RT performance and the long-term RT-SWIM or SWIM-RT training outcome has received limited attention. The existing studies indicate that acute RT or SWIM training may temporarily decrease subsequent muscle function. Concurrent application of RT-SWIM or SWIM-RT may induce similar physiological alterations. Such alterations are dependent on the recovery duration between sessions. Considering the long-term effects of RT-SWIM, the limited existing data present improvements in front crawl swimming performance, dry-land upper and lower body maximum strength, and peak power in swim turn. Accordingly, SWIM-RT training order induces swimming performance improvements in front crawl and increments in maximum dry-land upper and lower body strength. Concurrent application of RT-SWIM or SWIM-RT training applied within a training day leads in similar performance gains after six to twelve weeks of training. The current review suggests that recovery duration between RT and SWIM is a predisposing factor that may determine the training outcome. Competitive swimmers may benefit after concurrent application with both training order scenarios during a training cycle.